2020
DOI: 10.1186/s13046-020-01587-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein MSI2 isoforms expression and regulation in progression of triple-negative breast cancer

Abstract: Background: The RNA-binding protein Musashi-2 (MSI2) has been implicated in the tumorigenesis and tumor progression of some human cancers. MSI2 has also been reported to suppress tumor epithelial-to-mesenchymal transition (EMT) progression in breast cancer, and low MSI2 expression is associated with poor outcomes for breast cancer patients; however, the underlying mechanisms have not been fully investigated. This study investigated the expression and phenotypic functions of two major alternatively spliced MSI2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 41 publications
(52 reference statements)
4
32
1
Order By: Relevance
“…Many RBPs bind to sequence-speci c motifs or RNA secondary structures through unique modular arrangements of individual RNA-binding domains to play the roles in the homeostatic regulation of gene expression [24,25], which in uence the progression of many diseases. For example, RBP MSI2a expression alleviates triple-negative breast cancer invasive abilities through stabilizing TP53INP1 mRNA and inhibiting ERK1/2 activity [26]. RBP CASC9 interacts with hnRNPL form a complex to regulate DNA damage signal and PI3K/AKT signaling pathway, in uencing tumor cell proliferation and apoptosis in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many RBPs bind to sequence-speci c motifs or RNA secondary structures through unique modular arrangements of individual RNA-binding domains to play the roles in the homeostatic regulation of gene expression [24,25], which in uence the progression of many diseases. For example, RBP MSI2a expression alleviates triple-negative breast cancer invasive abilities through stabilizing TP53INP1 mRNA and inhibiting ERK1/2 activity [26]. RBP CASC9 interacts with hnRNPL form a complex to regulate DNA damage signal and PI3K/AKT signaling pathway, in uencing tumor cell proliferation and apoptosis in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…The MSI2 gene, physically located on chromosome 17q22, 10 produces four mRNA transcripts, resulting in 4 corresponding protein isoforms (MSI2a, MSI2b, MSI2c, MSI2d). 23 All of these four isoforms contain two conserved N-terminal RNA-recognition motifs (RRM1 and RRM2) but differ in the N-terminal or C-terminal amino acids. Biochemical and structural studies showed that the RRM1 contributes to the majority of the binding energy and specificity, while RRM2 has a more supportive role.…”
Section: Musashi-2 Protein Structure and Its Post-transcriptional Regmentioning
confidence: 99%
“…In addition, the effect of MSI2 in regulating specific mRNA translation differs depending on MSI2 protein isoforms, phosphorylation status, and cellular context. 23,[30][31][32][33] For example, Li et al demonstrated that overexpression of MSI2a in TNBC cells inhibits EMT, while MSI2b shows no significant effect in TNBC progression. 23 Similarly, ectopic expression of MSI2a, but not MSI2b, enhances the self-renewal capacity of embryonic stem cells (ESCs).…”
Section: Musashi-2 Protein Structure and Its Post-transcriptional Regmentioning
confidence: 99%
See 2 more Smart Citations